New kinematic and geochronologic evidence for the Quaternary evolution of the Central Anatolian fault zone (CAFZ). Issue 10 (9th October 2015) - Higgins, Mark; Schoenbohm, Lindsay M.; Brocard, Gilles; Kaymakci, Nuretdin; Gosse, John C.; Cosca, Michael A.
Abstract: As the kinematics of active faults that bound the Anatolian plate are well studied, it is now essential to improve our understanding of the style and rates of intraplate deformation to constrain regional strain partitioning and improve seismic risk assessments. One of these internal structures, the Central Anatolian fault zone (CAFZ), was originally defined as a regionally significant left‐lateral "tectonic escape" structure, stretching for 700 km in a NE direction across the Anatolian plate. We provide new structural, geomorphic, and geochronologic data for several key segments within the central part of the CAFZ that suggest that the sinistral motion has been overstated. The Ecemiş fault, the southernmost part of the CAFZ, has a late‐Quaternary minimum slip rate of 1.1 ± 0.4 mm a −1, slower than originally proposed. Farther north, the Erciyes fault has fed a linear array of monogenetic vents of the Erciyes stratovolcano and 40 Ar/ 39 Ar dating shows a syneruptive stress field of ESE‐WNW extension from 580 ± 130 ka to 210 ± 180 ka. In the Erciyes basin, and central part of the CAFZ, we mapped and recharacterized the Erkilet and Gesi faults as predominantly extensional. These long‐term geological rates support recent GPS observations that reveal ESE‐WNW extension, which we propose as the driver of faulting since 2.73 ± 0.08 Ma. The slip rates and kinematics derived in this study are not typical of an "escape tectonic" structure. The CAFZ is a transtensional fault system that reactivates paleotectonic structures and accommodates E‐W extension associated with the westward movement of Anatolia. Key Points: The CAFZ is a weakly active transtensional fault system Minimum sinistral slip rate of 1.1 ± 0.3 mm a −1 Evidence is presented which reveals ESE‐WNW extension since 2.73 Ma